Cross-sectional validity of the EQ-5D-Y as a generic health outcome instrument in children and adolescents with cystic fibrosis in Germany - Mittendorf Thomas; Eidt-Koch Daniela; Greiner Wolfgang (BMC, 2009)
Abstract Background Quality of life is recognized as an important additional outcome measure in clinical trials and health economic evaluations. The EQ-5D is an important generic health outcome instrument often used for economic evaluations as a complement with disease-specific outcome measures. In this study quality of life data was assessed using the EQ-5D-Y (new EQ-5D version for children and adolescents) and the Cystic Fibrosis Questionnaire (CFQ). The objective of the study is to evaluate the cross-sectional validity of the EQ-5D-Y as a generic health outcome instrument in children and adolescents with cystic fibrosis in Germany. Methods In 2006 a multi-centre study was conducted in four cystic fibrosis centres in Germany. Quality of life data from 96 patients between eight and seventeen years was collected using the EQ-5D-Y as a generic outcome instrument and the Cystic Fibrosis Questionnaire (CFQ) as a disease-specific instrument. Results of both instruments were compared by statistical analyses using Spearman's rank correlations. Results 44.6% of the patients stated that they had no problems in any of the EQ-5D-Y dimensions. Several low to high correlations between separate dimensions and the visual analogue scale of the EQ-5D-Y and the different scales of the CFQ for children, their parents and adolescents can be presented in this paper. Looking at the five EQ-5D-Y dimensions the highest correlation (rS = 0.625, p = 0.01) was found between the dimension 'mobility' and the CFQ scale 'physical functioning' in adolescent patients. The overall highest correlation was found between the 'subjective health perception' and the visual analogue scale (rS = 0.744, p = 0.01) in adolescent patients older than 13 years. Conclusion The EQ-5D-Y can be considered a cross-sectional valid generic health outcome instrument which reflects differences in health according to the progression of the life-long chronic disease cystic fibrosis.